1996
DOI: 10.1111/j.1365-2133.1996.tb16221.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide, endothelin-1, the cutaneous microvasculature and Raynaud's phenomenon

Abstract: It has been argued that the digital cutaneous microvasculature is the site of the anomaly which causes Raynaud's phenomenon (RP). Both endothelin-1 (ET-1), a potent vasoconstrictor peptide present in the digital cutaneous microvasculature, and calcitonin gene-related peptide (CGRP), a powerful vasodilator present in digital cutaneous perivascular nerves, have been implicated in the pathogenesis of RP. Circulating ET-1 levels are raised, and there is a diminution of CGRP-containing perivascular nerves in finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 37 publications
1
21
1
Order By: Relevance
“…Bunker et al showed the loss of CGRP containing nerve fibers (5), with decreased skin blood flow response to CGRP when fingers were exposed to cold (using an environmental chamber; Ref. 4). In the present study, the use of local anesthesia on the dorsum of the finger partially restored the transient vasodilation in participants with primary RP when cooling locally at 15°C.…”
Section: Discussionsupporting
confidence: 54%
“…Bunker et al showed the loss of CGRP containing nerve fibers (5), with decreased skin blood flow response to CGRP when fingers were exposed to cold (using an environmental chamber; Ref. 4). In the present study, the use of local anesthesia on the dorsum of the finger partially restored the transient vasodilation in participants with primary RP when cooling locally at 15°C.…”
Section: Discussionsupporting
confidence: 54%
“…86 Bunker et al have argued that, in normal subjects, the CGRP-containing digital cutaneous nerves are stimulated in response to cold and release CGRP which produces dilation, and helps to counteract cold-induced vasoconstriction. 87 Thus, they maintain that CGRP is a major contributor to cold-induced vasodilation. They further propose that ET-1, which others have shown is found released in response to cooling (see above), not only produces local constriction, but activates the CGRP-containing sensory nerves to produce vasodilation.…”
Section: Calcitonin Gene-related Peptide (Cgrp)mentioning
confidence: 99%
“…Raynaud's phenomenon usually is triggered by cold temperatures, or by emotions such as stress and anxiety (Cooke and Marshall, 2005). The pathological mechanisms are related to the high level of sympathetic activity (Stallworth et al, 1981;Sakakibara et al, 2002;Cooke and Marshall, 2005) and low level of CGRP expression in the local sensory fibers (Mourad and Priollet, 1997;Bunker et al, 1996). The island skin flap animal has been used to mimic the vasospastic condition (Linderoth et al, 1995 b;Qi et al, 2002).…”
Section: 15mentioning
confidence: 99%